2018
DOI: 10.1051/matecconf/201817101003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pore geometry of mesoporous supports on catalytic performances in methane reforming

Abstract: Abstract-Catalysts prepared using three dimensional SBA-16 silica support (composed of micropores and cage-like mesopores) were tested in the reaction of methane dry reforming, in comparison with 2D hexagonal mesoporous SBA-15 support. The samples were evaluated by N2 sorption and X-Ray diffraction (XRD) for the assessment of their textural and structural properties. The reducibility was characterized by temperature programmed reduction (TPR). The catalytic performances were evaluated in methane dry reforming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Table S1: Comparison of catalysts used in this work with previous literature. References [26][27][28][29][30][31][32][33][34] are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Table S1: Comparison of catalysts used in this work with previous literature. References [26][27][28][29][30][31][32][33][34] are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…17 El Hassan et al 18 proved high NiO nanoparticle dispersion inside SBA-15 pores through the impregnation method with two solvents. Tannous et al 19 reported the SBA-16 pore structure and its effect on catalytic activity and stability. They tried to develop better support nanomaterial in comparison with SBA-15.…”
Section: Introductionmentioning
confidence: 99%